In Vitro Analysis Of Antimicrobial Activity Of Stem Extracts Of Erythrina Variegata L: A Useful Medicinal Plant - K. SAHOO,; S.S PANDA,; S.S PANDA,; D. DAS,; N.K DHAL, (International Journal of Pharma and Bio Sciences, 2012)
Antimicrobial activity of methanolic, chloroform, hexane and aqueous stem extracts of Erythrina variegata L. were analyzed against nine bacterial pathogens such as Salmonella typhi, Pseudomonas putida, Pseudomonas aeruginosa, Escherichia coli, Klebsiella sp., Proteus sp., Serratia marcescens, Bacillus circulans, Staphyloccus aureus and five fungal pathogens viz. Aspergillus niger, Aspergillus fumigatus, Sclerotium sp., Rhizopous sp., Candida sp. Among all the strains, few strains like Serratia marcescens , E.coli, Pseudomonas putida, Bacillus circulans was found to be more susceptible strains and among all the solvent extracts methanol showed promising antimicrobial activity. The results obtained in this study suggested that the stem extract of Erythrina variegate L. have high potential for use in the treatment of diseases caused by these test organisms.